Peningkatan Kualitas Lingkungan Hidup Yang Aman, Bersih dan Tertata di Perumahan Taman Alamanda RW 012 Desa Karang Satria Kecamatan Tambun Utara Kabupaten Bekasi - Rukmayadi, Dede; Abdurrafi, Adhe; Martapiadi, Andika; Priatna, Ardhani; Huda, Rowi Ali; Rudi; Nugraha, Taufik Rizki; Adhiatama, Alvian; Baihaqi, Andhika Ariq; Andhika Seti (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2025)
The 2023 Community Service Program (KKN) conducted by Universitas Bhayangkara Jakarta Raya at Taman Alamanda Housing, RW 012, Karang Satria Village, aimed to improve the quality of a safe, clean, and well-organized living environment. The main issues addressed included the community’s low awareness of waste management and the absence of adequate traffic signs. Through a participatory approach, the KKN activities focused on three main programs: (1) the installation of environmentally friendly waste bins based on waste types (organic and inorganic), (2) painting of speed bumps (“sleeping police”) as traffic safety markers, and (3) community clean-up activities to foster a culture of mutual cooperation. The implementation methods included observation, interviews, and active student engagement as facilitators. The results demonstrated increased public awareness and participation in maintaining a clean and safe environment while also strengthening social bonds within the community. The program delivered tangible benefits for both residents and students and is expected to be sustained by the local community in the long term.